Health problems account for a small part of the association between socioeconomic status and disability pension award. Results from the Hordaland Health Study - Reichborn-Kjennerud Ted; Knudsen Ann; Ørstavik Ragnhild E; Østby Kristian; Mykletun Arnstein (BMC, 2011)
Abstract Background Low socioeconomic status is a known risk factor for disability pension, and is also associated with health problems. To what degree health problems can explain the increased risk of disability pension award associated with low socioeconomic status is not known. Methods Information on 15,067 participants in the Hordaland Health Study was linked to a comprehensive national registry on disability pension awards. Level of education was used as a proxy for socioeconomic status. Logistic regression analyses were employed to examine the association between socioeconomic status and rates of disability pension award, before and after adjusting for a wide range of somatic and mental health factors. The proportion of the difference in disability pension between socioeconomic groups explained by health was then calculated. Results Unadjusted odds ratios for disability pension was 4.60 (95% CI: 3.34-6.33) for the group with elementary school only (9 years of education) and 2.03 (95% CI 1.49-2.77) for the group with high school (12 years of education) when compared to the group with higher education (more than 12 years). When adjusting for somatic and mental health, odds ratios were reduced to 3.87 (2.73-5.47) and 1.81 (1.31-2.52). This corresponds to health explaining only a marginal proportion of the increased level of disability pension in the groups with lower socioeconomic status. Conclusion There is a socioeconomic gradient in disability pension similar to the well known socioeconomic gradient in health. However, health accounts for little of the socioeconomic gradient in disability pension. Future studies of socioeconomic gradients in disability pension should focus on explanatory factors beyond health.